FUNCTIONAL LOADING OF REMARKS IN DRAMATURGIC TEXT (ON THE MATERIAL OF THE UKRAINIAN DRAMA OF THE END OF THE XIX – BEGINNING OF THE XX CENTURY) - Іванишин, Н. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights implicit-oriented peculiarities of the remarks in dramaturgic text and the specificity of its implicitness actualization in the drama texts of the end of the 19th beginning of the 20th century.